Characteristics of Tolerance in Believers of Russian Orthodox and Islamic Identification - Z G Rashidova (Peoples' Friendship University of Russia (RUDN University), 2011)
The psychological peculiarities of tolerance in Russian Orthodox and Islamic believers are revealed in the article, their comparative analysis is conducted.